Pendidikan Komunikasi dalam terang Misi sebagai Dialog Profetis - Soge, Aurelius Pati (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2007)
Living in a plural society like today, the Church is challenged to update its mission in order to meet the need of the society. The plurality has served as a new context of the mission which the Church is obliged to bring about. While the idea of spreading the Good News remains intact, the methods need to be updated. It has to change along with the social development. There are various responses the Church has initiated for years, however, the actual need is very much shaped by the model of dialog. The dialog requires the change of mentality, as every person engaged in this process is considered partner, which means